Implementasi Strategi Pemasaran dalam Rangka Meningkatkan Jumlah Peserta Didik di Brilliant English Course - Hadi Cipto Sanyoto; Petty Arisanti (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze marketing strategic at Brilliant English Course, then to know the analyze strategic which is on progress and strategy description so that it can be applied to increase product sales. This research uses qualitative method that is case study which produce descriptive data which poured in words. Data collection technique in this study author make direct visits to Brilliant English Course to conduct a personal interview with the Director of Brilliant English Course marketing and completed with the information data several years behind. The conclusion of the analysis conducted on marketing strategy correctly and precisely. Which companies can develop, maintain and improve product quality so that people continue to believe in Brilliant English Course. Then the company has fulfilled the character and paradigm of sharia marketing by winning mind share, market share and heart share